Electron-beam radiation induced degradation of silicon nitride and its impact to semiconductor failure analysis by TEM - Liu, Binghai (2019)
By in-situ transmission electron microscopy (TEM), we performed a detailed study on the electron-beam radiation damage to nanostructured silicon nitride thin-film process layers in a typical semiconductor NVM device. It was found that high-dose electron-beam radiation at 200 kV led to rapid degradation of silicon nitride process layers, i.e. thin-downing of nanostructured silicon nitride, inter-diffusion of O and N, the formation of bubble-like defects and segregation of N at neighbouring interfaces. Further detailed analysis revealed that radiation-induced modification in the microstructure and chemical composition of silicon nitride layers could be ascribed to the electron radiation induced knock-on damage and ionization damage. The radiation enhanced diffusion (RED) accounted for the continuous thin-down of the nitride process layer and the formation of bubble-like defects in thick nitride spacer process layers. The work well demonstrated the electron-beam sensitivity of nanostructured silicon nitride materials in the semiconductor devices, and thus may give useful information about electron-dose control during TEM failure analysis of the semiconductor devices containing nanostructured silicon nitride process layers.